Strategi Pemasaran KPRS Bank Syariah Mandiri - Maulida Itsni Zumayjah; Mas Deden Tirtajaya (At-Tamwil: Journal of Islamic Economics and Finance, 2022)
This study aims to identify and analyze the most appropriate marketing strategy for KPRS Bank Syariah Mandiri Bekasi Area so as to win the competition. This study uses a SWOT analysis with IFAS and EFAS matrices to identify important factors, both from the external environment and the internal environment, which are the strengths, weaknesses, opportunities and threats of Griya Berkah financing products. The research approach used in this study is a descriptive qualitative approach. The results of this study will be analyzed in addition to descriptive qualitative, the author also uses a SWOT analysis. SWOT analysis is the identification of various factors systematically to formulate corporate strategy. From the results of the analysis based on the IE matrix, a growth and build strategy is obtained, this strategy indicates a strong company condition and is able to continue to grow by taking the opportunities or opportunities that exist to achieve maximum turnover. This study resulted in a total of 2,316 Strength Weakness 0.700 Opportunity 1,608 Threats 0.687 from Griya Berkah financing products where the company's position is in quadrant l (one). The appropriate strategy in this quadrant based on the Cartesian diagram is development / aggressive strategy by carrying out expansion, enlarging growth and achieving maximum progress.